Politicization of Bureaucracy in the Mutation of Career Officials Ahead of the 2024 Election in South Halmahera Regency - Sumitro Sy. Syawal; Sukur Suleman; Fitria Djarre (Journal of Research in Social Science and Humanities, 2026)
The politicization of bureaucracy in the implementation of career official mutations in South Halmahera Regency began after the death of Regent Usman Sidik on November 5, 2023. Subsequently, Deputy Regent Ali Bassam Kasuba was appointed as Acting Regent of South Halmahera based on the Governor of North Maluku’s decree dated November 6, 2023, Number: 100.1.4.2/3665/G. Previously, both were elected as a political pair in the 2020 regional election as Regent and Deputy Regent. Bureaucratic politicization also occurred ahead of the 2024 general election, where several relatives of the Acting Regent—including his uncle, cousins, and younger sibling—ran as legislative candidates at both national and regional levels. Career officials who sought to obtain or maintain certain bureaucratic positions attempted to engage in political activities, which subsequently generated bureaucratic politicization. Furthermore, mutations were also carried out after the election, as officials who were transferred were considered to have contributed insufficiently during the 2024 election. Therefore, maintaining bureaucratic neutrality from political interests becomes extremely difficult. Instead, bureaucracy tends to be absorbed into political dynamics during elections and regional head contests. If bureaucrats refrain from engaging in political activities, they risk negative implications resulting from politicization. This study aims to identify the relationship pattern between political officials and career officials in the mutation of career officials and to examine the implications of bureaucratic politicization following the implementation of such mutations. This research employs a qualitative method with a phenomenological approach. Data were obtained through observation, in-depth interviews, documentation, and secondary data from document tracing. Data analysis uses the qualitative analysis model of Miles and Huberman, which includes data collection, data reduction, data display, and conclusion drawing and verification.